Strategic Planning for Systems & Information Technology of XYZ Hospital Using Ward and Peppard Method - I Made Candra Girinata; Erma Suryani (IPTEK Journal of Proceedings Series, 2019)
XYZ Hospital is one of the busiest private hospitals in Badung, Bali which has implemented systems and information technology handled by its IT division staff. However, the implementation of systems and information technology has not been equipped with strategic planning so that it has not been directed and aligned with the company's business strategy, only based on demand. The impacts of there's no strategic planning systems and information technology is the companies are difficult to invest appropriately based on system requirements and information technology that can support the company's business strategy. Increasing the competitive advantage of utilizing systems and information technology still not optimal because the development of IS / IT lack directional and appropriate. Therefore, to overcome the problems, in this research is making strategic planning of systems and information technology of XYZ hospital, which carried out with Ward and Peppard method which serves to produce an IS /IT strategic plan that can help the company to run their process business more effectively as well as add its business value. The analysis techniques used are Value Chain, PEST, Porter 's Five Forces, SWOT, BSC, CSF, gap analysis and Mc Farlan's Strategic Grid. From the results of the analysis of the current condition of the company shows that XYZ Hospital is in the position of quadrant 1 which indicates the company should be focused on an aggressive strategy where reduce weaknesses and avoid threats to get maximum benefit. The recommendations for future application portfolios obtained are three applications in the high potential quadrant, one application in the strategic quadrant and two applications in the key operational quadrant. The results of this study aim to provide an overview to management in making decisions relating to investment, implementation and management policies of IS / IT that can support the company's vision and mission